Direct Catalytic Conversion of Carbon Dioxide to Liquid Fuel at Ambient Temperature: A Novel Metal-Organic Framework Approach - Eka Cahya Muliawati (CV. Get Press Indonesia, 2024)
The increasing concentration of atmospheric CO₂ has prompted the development of efficient strategies for carbon capture and utilization. In this study, a novel bimetallic Cu-Zn/ZT metal-organic framework (MOF) was synthesized and evaluated for direct hydrogenation of CO₂ to methanol and ethanol at ambient temperature (30°C) and 1 atm. The Cu-Zn/ZT catalyst exhibited superior activity compared to monometallic analogs, achieving a CO₂ conversion of 12.5% with 78% selectivity toward methanol and 15% toward ethanol. Characterization revealed a highly crystalline framework, uniform mesoporosity ( 1.2 nm), and synergistic Cu⁺/Zn²⁺ active sites that facilitate H₂ activation and CO₂ adsorption. The catalyst demonstrated good stability and reusability over five cycles, retaining high selectivity. These findings highlight the potential of rationally designed bimetallic MOFs for energy-efficient CO₂-to-liquid-fuel conversion under mild conditions, offering a promising route for sustainable carbon utilization